The role of women in fezzan the middle ags (Journal of Human Sciences, 2025)
This study, entitled “The Role of Women in the Fezzan Region during the Medieval Period,” seeks to shed light on the status of women in Fezzan and the diverse political, economic, and social roles they assumed, as well as the rights they enjoyed during the Middle Ages. Its significance lies in addressing a subject that has received limited scholarly attention, apart from scattered references in a few historical sources that nonetheless preserve valuable insights. The research adopts an inductive historical methodology combined with textual analysis of archival and documentary sources pertaining to Fezzani women. The available fragments were systematically collected, examined, and interpreted.The thesis is structured into an introduction followed by three main chapters. Chapter One investigates women’s political roles, focusing on their participation in regional governance and their influence during the Ottoman era. Chapter Two explores women’s economic contributions, including their involvement in trade, agriculture, traditional crafts, and the production of adornments and jewelry. Chapter Three examines their social roles, highlighting examples of women’s rights in Fezzan and the functions they fulfilled within their communities. The study concludes by presenting its key findings, followed by a comprehensive list of sources and references.